Perlindungan Hukum Bagi Investor Dalam Penanaman Modal di Indonesia - Terania, Medi; Lie, Gunardi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Foreign direct investment is fundamental to supporting the financing of Indonesia’s national development, playing a role in driving economic growth, technology transfer, and job creation. The government has regulated Safeguards established by law for investors through Law No. 25 of 2007 on Investment, That offers a clear and stable legal framework, non-discriminatory treatment, asset protection, and ease of repatriation of capital and profits. However, in practice, foreign investors still face various challenges and legal risks, such as regulatory uncertainty, disputes with the government, bureaucratic obstacles, political and social risks, and inconsistent law enforcement. The research follows a normative approach to legal analysis method with a literature review to evaluate the existing forms of legal protection and the challenges faced by foreign investors in Indonesia. The research underlines the essential nature of improved regulatory consistency, bureaucratic simplification, fair law enforcement, and political stability in order to create a conducive investment climate. Thus, effective legal protection can increase Indonesia's attractiveness as a safe and sustainable investment destination and support inclusive national development.